The Influence Of Principal Leadership And Socio-Emotional Competence On Teacher Performance At State Middle School 1 Ratahan - Sofiana Boroni; Shelty DM Sumual; Joulanda AM Rawis (PT. AHLAL PUBLISHER NUSANTARA, 2026)
SOFIANA BORONI, 2026. The Influence of Principal Leadership and Social-Emotional Competence on Teacher Performance at SMP Negeri 1 Ratahan. Thesis. Graduate Program of UNIVERSITAS NEGERI MANADO. Supervisors: (1) Prof. Dr. Shelty DM Sumual, M.Si, (2) Prof. Dr. Joulanda AM Rawis, M.Pd. This research is motivated by the critical role of instructional leadership and educators' emotional maturity in enhancing the quality of learning. The study aims to analyze: (1) the influence of Principal Leadership on Teacher Performance; (2) the influence of Social-Emotional Competence on Teacher Performance; and (3) the simultaneous influence of both Principal Leadership and Social-Emotional Competence on Teacher Performance at SMP Negeri 1 Ratahan.The research method employed is quantitative with a causal-associative approach. The population for this study consists of all teachers at SMP Negeri 1 Ratahan, totaling 30 individuals. The sampling technique used is Total Sampling. Data were collected using Likert scale questionnaires that have been tested for validity and reliability. Data analysis was performed using Product Moment correlation and multiple linear regression analysis with the assistance of SPSS software.The results indicate that: (1) there is a positive and significant influence of Principal Leadership on Teacher Performance, with a t_count of 3.067 > t_table of 2.051 and a significant value of 0.004 < 0.05; (2) there is a positive and significant influence of Social-Emotional Competence on Teacher Performance, with a t_count of 4.282 >t_table of 2.051 and a significant value of <0.05; (3) simultaneously, Principal Leadership and Social-Emotional Competence significantly influence Teacher Performance, contributing 58% to the teacher performance variable, while the remaining 42% is influenced by other factors not examined in this study. The conclusion of this research emphasizes that effective principal leadership, supported by teachers' social-emotional maturity, is a key factor in optimizing teacher performance at SMP Negeri 1 Ratahan. Keywords: Principal Leadership, Social-Emotional Competence, Teacher Performance.